The Effect of Chlorhexidine on the Push-Out Bond Strength of Calcium-Enriched Mixture Cement - Sobhnamayan, Fereshte; Adl, Alireza; Sadat Shojaee, Nooshin; Gavahian, Samina (Iranian Endodontic Journal, 2014)
Introduction: The aim of this in vitro study was to evaluate the effect of 2% chlorhexidine (CHX) on the push-out bond strength (BS) of calcium-enriched mixture (CEM) cement. Methods and Materials: Root-dentin slices from 60 single-rooted human teeth with the lumen diameter of 1.3 mm were used. The samples were randomly divided into 4 groups (n=15), and their lumens were filled with CEM cement mixed with either its specific provided liquid (groups 1 and 3) or 2% CHX (groups 2 and 4). The specimens were incubated at 37°C for 3 days (groups 1 and 2) and 21 days (groups 3 and 4). The push-out BS were measured using a universal testing machine. The slices were examined under a light microscope at 40× magnification to determine the nature of bond failure. The data were analyzed using the two-way ANOVA. For subgroup analysis the student t-test was applied. The level of significance was set at 0.05. Results: After three days, there was no significant difference between groups 1 and 2 (P=0.892). In the 21-day specimens the BS in group 3 (CEM) was significantly greater than group 4 (CEM+CHX) (P=0.009). There was no significant difference in BS between 3 and 21-day samples in groups 2 and 4 (CEM+CHX) (P=0.44). However, the mean BS after 21 days was significantly greater compared to 3-day samples in groups 1 and 3 (P=0.015). The bond failure in all groups was predominantly of cohesive type. Conclusion: Mixing of CEM with 2% CHX had an adversely affected the bond strength of this cement.